Ultra-flat giant grain Cu film atop α-Al2O3 (0001) for apCVD synthesis of graphene - Roberts, Floyd (2018)
Graphene microelectronic devices are still in the research phase. Consistent production of such small-scale structures requires increasingly higher quality graphene. Commonly, graphene is grown by chemical vapor deposition (CVD) on the surface of a substrate catalyst. Defects on the catalyst are known to generate corresponding defects in the CVD graphene grown atop it. The current study seeks to produce a wafer scale single-crystal Cu thin film supported by Al2O3 which is durable enough for apCVD graphene production.